Математическая модель гидродинамики движения двухфазного восходящего потока в пневмоклассификаторах переменного сечения - Литвиненко, Андрей Владимирович; Юхименко, Николай Петрович (НТУ "ХПИ", 2016)
Процессы классификации заключаются в разделении сыпучих материалов на две и более фракции по размеру частиц, причем содержание примесей в этих продуктах допускается в небольшом количестве. Высокая степень разделения при осуществлении процессов классификации дисперсных материалов влияет не только на расходные нормы сырья и его качество, но и определяет производительность и эффективность работы других машин и аппаратов в технологической схеме, в конечном итоге сказывается на технике - экономических показателях всего производства. Данная работа посвящена созданию математической модели гидродинамики движения двухфазного потока. Описана математическая модель однофазного потока (газовая фаза). Так же описана математическая модель двухфазного потока, на примере газовой фазы и твёрдой частицы.

Classification processes involve division of granular materials into two and more fractions according to the particles size. Notably, impurity content in these products is acceptable in small amounts. The high separation level during the particulates classification processes affects not only the raw materials unit consumption and its quality but also has an impact on the productivity and efficiency of other machines and apparatus in the flowsheet and, eventually, on the technical-and-economic indicators of the production in general. This paper deals with the developing the hydrodymamics mathematical model of two phase flow motion. To reach the set goal, the authors created the mathematical model of one phase flow (gas phase). The next stage was the creation of the mathematical model of two phase flow, as exemplified by the gas phase and the solid particle. This model is unique due to the fixation of the dependence of solid particles velocity on the apparatus body and the gas flow profile. The authors worked out the equations to define the velocity of the gas flow and the velocity of the solid particle at every point of the variable cross-section apparatus body. The authors developed the characteristic curve of gasflow line in the pneumatic classifier body. The solid particle trajectories were defined in the body of the pneumatic classifier with variable cross-section. The velocity distribution and the influence of the gas flow on the individual solid particle are deeply analyzed in the paper. The conclusions also deal with the trajectory change of the individual particle within the apparatus body.
The mathematical model of hydrodynamics motion of two phase ascending flow in pneumatic classifiers of variable cross-section
Keywords: траектория; скорость витания; профиль скорости; частицы; particle; terminal velocity; velocity profile